Solar-radiation-absorbing formulations, application of paint, painted metal article and related apparatus. - Magdassi, Shlomo; Mandler, Daniel; Baidossi, Mubeen; Assa, Rachel; Chernin, Ophir; Binyamin, Yaniv. (U.S. Pat. Appl. Publ., 2014)
Paint formulations having a high absorptivity with respect to solar radiation are described. The paint formulations are also thermally and mech. durable, enabling the paint formulations to be used on components in solar thermal applications where exposure to high temps. and environmental conditions may be an issue. The paint formulation can include an oxide-based pigment, an org. binder, >=1 additives, an inorg. filler, and/or an org. solvent. The pigment can have a relatively high absorptivity with respect to light having a wavelength in the range 250-3000 nm. Curing of the paint formulation can irreversibly convert the org. binder into an inorg. binder. [on SciFinder(R)]
CAPLUS AN 2014:830676(Patent)
Keywords: ceramic oxide pigment paint solar radiation absorbing